BRAND SWITCHING BEHAVIOUR IN THE GENERATION Y: EMPIRICAL STUDIES ON SMARTPHONE USERS - Indah Fintikasari; Elia Ardyan (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
Lifestyle, variety seeking, customer trust and promotion are some factors that can be a trigger. The sample of respondents used in this study is 385 respondents’ smartphone users who have experience of brand switching, while the analysis of this study using structural equation modelling (SEM) and to process this research data used AMOS version 20. The result indicated that lifestyle and variety seeking is able to increase brand switching, especially on smartphone product users. Consumer trust in a particular brand still unable to reduce their desire to switch brand significantly, another result also indicated that promotion unable to increase the desire to switch brands.